Private Higher Education Quality Development Strategy in Improving Competitiveness - Suaibatul Aslamiyah (Universitas Muhammadiyah Sorong, 2026)
Higher education is an integral part of the national education system that plays a vital role in educating the nation and encouraging the advancement of science and technology. In carrying out its role, higher education continues to prioritize humanistic values and the sustainable empowerment of Indonesian society. Higher education also serves to increase the nation's competitiveness in facing global challenges in various fields. The effective implementation of quality assurance will have a positive impact, both directly and indirectly, on the higher education institution. One of the private universities in Gresik that has consistently improved its quality and competitiveness is Muhammadiyah University of Gresik. This research uses a qualitative case study approach. The results show that the consistent alignment of internal (SPMI) and external (SPME) quality has made a real contribution to the university and its study programs. This is evidenced by external recognition from the university in the form of achieving the number 1 ranking for the best university in Gresik and several study programs being accredited as